Understanding Contextual Spillover: Using Identity Process Theory as a Lens for Analyzing Behavioral Responses to a Workplace Dietary Choice Intervention - Verfuerth, Caroline; Jones, Christopher R.; Gregory-Smith, Diana; Oates, Caroline (Frontiers in Psychology, 2019)
Spillover occurs when one environmentally sustainable behaviour leads to another, often initiated by a behaviour change intervention. A number of studies have investigated positive and negative spillover effects, but empirical evidence is mixed, showing evidence for both positive and negative spillover effects, and lack of spillover altogether. Environmental identity has been identified as an influential factor for spillover effects. Building on identity process theory the current framework proposes that positive, negative, and a lack of spillover are determined by perceived threat of initial behaviour and identity process mechanisms evaluating the behaviour. It is proposed, that an environmental behaviour change intervention may threaten one’s existing identities, leading to either (a) integration, (b) compartmentalisation, or (c) conflict between one’s environmental identity and non-environmental identities. Initial evidence for the proposed framework is based on a field intervention which included a meat reduction programme in a canteen of a medium size private sector company. Semi-structured interviews and an explorative visualisation method that aimed at assessing identity change were implemented with thirteen employees (i.e. intervention participants) before and after the intervention. The qualitative data was analysed by using thematic analysis via NVivo12. Results of the visualisation task and interview method provided initial evidence of direct and indirect positive contextual spillover effects, with comparatively less evidence a lack of spillover and a relative absence of reported negative spillover. This paper provides a novel theoretical approach, centred on identity process theory to enhance understanding of positive spillover, negative spillover, and the lack of spillover.